Internal and external load profiles of male basketball players during training - García-Rubio, J.; López-Sierra, P.; Reina, M.; Ibañez, S. J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2026)
Traditionally in basketball, five specific positions have been distinguished, often due to the anthropometric characteristics of the players. In recent years, different research has emerged that tries to break with this paradigm, giving rise to different classifications of players based on other characteristics that are more closely related to the actual game of basketball. The aim of this research was to determine the load profiles of players according to internal and external load values. An observational design was used, in which 12 professional players from the Spanish Men`s First Division Basketball (ACB league) team participated, obtaining data from all the training sessions carried out over two microcycles. All players were equipped with WIMUPRO™ inertial devices, using a UWB system for the players` positioning in indoor spaces. A principal component analysis with varimax rotation was performed to group the variables and determine the profiles. The results showed four different player profiles: versatile, explosive, dynamic, and fast players. Within these load profiles are included players from the five specific positions according to the traditional basketball classification, possessing distinct anthropometric characteristics among themselves. These results allow strength and conditioning coaches to train players physically in a more efficient way, using small-sided games in mid court, or games in full court more adequately, and achieving greater specificity and applicability in their exercises and tasks.